LANGGAM DAN ZAPIN GRUP MUSIK MELAYU SAYANG SENANDUNG - Yusnelli Yusnelli; Ferry Herdianto (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2021)
Malay art generally displays songs that have song ranges or tempo such as langgam and zapin. Likewise with the Malay art of Sayang Senandung always plays these two tempos in every show. However, there is something unique about Sayang Senandung where the two tempo forms are packaged using different instruments from other Malay forms. Tempo Langgam uses violin instruments (melodic instruments), bebano pasu, kompang, and tetawak as tempo control instruments, and in every show always plays the songs Dondang Sayang, Inang Cina and Serampang Laut. Tempo Zapin uses the string instrument, the violin as the carrier of the melody and filler and the Marwas and the tetawak as the instrument for cntrolling the tempo. The songs he often performed were zapin major and zapin minor.